Quantitative analysis of intraventricular flow-energetics and vortex in ischaemic hearts. Issue 4 (June 2018) - Chan, Bee Ting; Yeoh, Hak Koon; Liew, Yih Miin; Dokos, Socrates; Al Abed, Amr; Chee, Kok Han; Abdul Aziz, Yang F.; Sridhar, Ganiga Srinivasaiah; Chinna, Karuthan; Lim, Einly
Abstract : Objective: This study investigated the intraventricular flow dynamics in ischaemic heart disease patients. Patients and methods: Fourteen patients with normal ejection fraction and 16 patients with reduced ejection fraction were compared with 20 healthy individuals. Phase-contrast MRI was used to assess intraventricular flow variables and speckle-tracking echocardiography to assess myocardial strain and left ventricular (LV) dyssynchrony. Infarct size was acquired using delayed-enhancement MRI. Results: The results obtained showed no significant differences in intraventricular flow variables between the healthy group and the patients with normal ejection fraction group, whereas considerable reductions in kinetic energy (KE) fluctuation index, E ′ ( P <0.001) and vortex KE ( P =0.003) were found in the patients with reduced ejection fraction group. In multivariate analysis, only vortex KE and infarct size were significantly related to LV ejection fraction ( P <0.001); furthermore, vortex KE was correlated negatively with energy dissipation, energy dissipation index ( r =−0.44, P =0.021). Conclusion: This study highlights that flow energetic indices have limited applicability as early predictors of LV progressive dysfunction, whereas vortex KE could be an alternative to LV performance.